2012
DOI: 10.1111/j.2042-7158.2012.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-mediated pro-apoptotic interaction of panaxadiol and irinotecan in human colorectal cancer cells

Abstract: Objectives Panaxadiol (PD) is a purified sapogenin of ginseng saponins that exhibits anticancer activity. Irinotecan (IRN) is a second line anticancer drug, but clinical treatment with IRN is limited due to side effects. In this study, we investigated the possible synergistic anticancer effects of PD and IRN on human colorectal cancer cells and explored the potential role of apoptosis in the synergistic activities. Key findings The combination of PD and IRN significantly enhanced antiproliferative effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In recent decades, natural products and their derivatives including paclitaxel (Khanna, Rosenberg, & Vail, ) and matrines (Yong, Wu, & Lu, ) with high anticancer bioactivity have been developed into anticancer agents for clinical use. Panaxadiols are the principal components of total saponins of FBP, and some reports have demonstrated their important role in enhancing antiproliferative effects and apoptotic induction during the treatment of human colorectal cancer cells with irinotecan and 5‐fluorouracil (Du et al, ; Li et al, ). In addition, some studies have demonstrated anticancer activities of FBP.…”
Section: Pharmacologymentioning
confidence: 99%
“…In recent decades, natural products and their derivatives including paclitaxel (Khanna, Rosenberg, & Vail, ) and matrines (Yong, Wu, & Lu, ) with high anticancer bioactivity have been developed into anticancer agents for clinical use. Panaxadiols are the principal components of total saponins of FBP, and some reports have demonstrated their important role in enhancing antiproliferative effects and apoptotic induction during the treatment of human colorectal cancer cells with irinotecan and 5‐fluorouracil (Du et al, ; Li et al, ). In addition, some studies have demonstrated anticancer activities of FBP.…”
Section: Pharmacologymentioning
confidence: 99%
“…The process of apoptosis is regulated by several proteins that either inhibit or promote apoptotic cell death. Caspase-9 and caspase-3, members of the cysteine protease family, are considered to be the central proteins in the execution of apoptosis (Bhardwaj et al, 2003;Du et al, 2012) while survivin is a identified member of the inhibitor of apoptosis protein family (Idenoue et al, 2005). Suzuki and Shiraki (2001) reported that survivin plays an important role in the suppression of apoptosis by either directly or indirectly inhibiting the activity of caspases.…”
Section: Introductionmentioning
confidence: 99%
“…Increased caspase 3 and caspase 9 activities were observed after treatment with both compounds, suggesting that the apoptosis was caspase-related cell death. The synergistic apoptotic effects were also supported by docking analysis, which demonstrated that panaxadiol and irinotecan bound two different chains of the caspase 3 protein (Du et al , 2012). …”
Section: Botanicals As Adjuvants For Cancer Chemopreventionmentioning
confidence: 79%
“…Because the combined use of irinotecan and panaxadiol significantly upregulated the expression of caspase 3, the Surflex-Dock program was used to determine the binding sites of panaxadiol and irinotecan to caspase 3. The binding affinities of test compounds to different binding sites were also determined, along with the locations of the hydrogen bonds formed (Du et al , 2012). …”
Section: Botanicals As Adjuvants For Cancer Chemopreventionmentioning
confidence: 99%